1970
DOI: 10.1017/s0043174500034573
|View full text |Cite
|
Sign up to set email alerts
|

Plant Litter and Establishment of Alien Annual Weed Species in Rangeland Communities

Abstract: Plant litter that covers the soil surface acts as a layer of insulation moderating temperature and moisture, and creating favorable microsites for germination and the establishment of annual weed species in rangeland communities. Litter cover is an important factor in succession among annual species which culminates in dominance by downy brome (Bromus tectorumL.) and medusahead (Taeniatherum asperum(Sim.) Nevski) in these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 10 publications
4
107
2
Order By: Relevance
“…The negative effects of litter on seedling growth or survival were unexpected, given the potential of litter to shade the soil and hence to reduce evaporation. Litter has been shown to increase seedling survival in arid environments (Evans and Young 1970).…”
Section: The Effects Of Litter and Rocksmentioning
confidence: 99%
“…The negative effects of litter on seedling growth or survival were unexpected, given the potential of litter to shade the soil and hence to reduce evaporation. Litter has been shown to increase seedling survival in arid environments (Evans and Young 1970).…”
Section: The Effects Of Litter and Rocksmentioning
confidence: 99%
“…The combination of positive and negative effects can also vary among different plant species and different conditions (Rotundo and Aguiar, 2005). Thus, while litter has generally been found to promote increased germination in arid areas (Evans and Young, 1970;Milton, 1995), other studies have shown little or no effect on germination (Eldridge and Westoby, 1991;Fowler, 1988;Hastwell and Facelli, 2000). Results are likely dependent on the amount of litter present and the length of time that litter has been decomposing in the pit.…”
Section: Discussionmentioning
confidence: 99%
“…This response is not unusual because germination and emergence of many forbs is greatest on bare soils (Bai and Romo, 1996;Evans and Young, 1970;Goldberg and Werner, 1983). Wide diurnal temperature fluctuations in bare soil can trigger germination and emergence of species with limited capacity to emerge from deep in the seed bank (Probert, 2000).…”
Section: Forbsmentioning
confidence: 99%
“…Wide diurnal temperature fluctuations in bare soil can trigger germination and emergence of species with limited capacity to emerge from deep in the seed bank (Probert, 2000). Furthermore, even though removing clubmoss usually reduced soil water content, the water content and relative humidity of bare soils tends to fluctuate more than surfaces covered by plant material as noted by Evans and Young (1970). These wetting and drying cycles can break dormancy and increase germination in seeds of many species (Baskin and Baskin, 1998;Oomes and Elberse, 1976).…”
Section: Forbsmentioning
confidence: 99%
See 1 more Smart Citation